2006
DOI: 10.1007/s11062-006-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional effects of applications of glutamate and dopamine on the goldfish Mauthner neurons

Abstract: In the goldfish, we studied the effects of intramedullar applications of glutamate (Glu), dopamine (DA), and of long-lasting rotational stimulation on the functional activity, dimensional characteristics, and ultrastructure of Mauthner neurons (MNs). Applications of Glu, especially when combined with rotational stimulation, were found to result in suppression of the function of MNs, in a decrease in their dimensions and lengths of desmosome-like contacts (DLCs, whose structure is determined by filamentous acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…According to the results of model studies, globular actin serves as the target and substrate for DA-induced direct formation of ¿ laments [1,4,5]. Hence, the effects of DA on BHK-21 cell viability and morphology, observed in our experiments, can be explained by the direct polymerizing effect of DA on cytoplasmic globular actin.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…According to the results of model studies, globular actin serves as the target and substrate for DA-induced direct formation of ¿ laments [1,4,5]. Hence, the effects of DA on BHK-21 cell viability and morphology, observed in our experiments, can be explained by the direct polymerizing effect of DA on cytoplasmic globular actin.…”
Section: Resultssupporting
confidence: 59%
“…Hence, the effects of DA on BHK-21 cell viability and morphology, observed in our experiments, can be explained by the direct polymerizing effect of DA on cytoplasmic globular actin. Previously detected ɫhanges in cell shape and hypertrophy of the cell cortical layer in lactotropes and desmosome-like contacts of Mauthner neurons [1,13] can be interpreted from this standpoint. Ultrastructural data on DAinduced hypertrophy of ¿ lamentous actin network in BHK-21 cell cytoplasm (more detailed data in [6]) and recent cytochemical data on DA penetration into BHK-21 cells and its integration in the actin ¿ laments [7] con¿ rm the possibility of non-ligand (trophic) DA interactions with living cells, as was assumed previously.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A technique of application of physiologically active substances to the MNs, which was developed earlier, allows us to realize such an examination [3,4]. Using this technique, experimenters have recently studied the effect of application of dopamine to the MNs [5]; this agent, as is known, is capable of inducing LTP at mixed MN synapses [6]. The data obtained demonstrated that ultrastructural manifestations of potentiation mediated by the action of dopamine or tetanic electrical stimulation of the corresponding afferent inputs in vitro are practically identical [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, experimenters have recently studied the effect of application of dopamine to the MNs [5]; this agent, as is known, is capable of inducing LTP at mixed MN synapses [6]. The data obtained demonstrated that ultrastructural manifestations of potentiation mediated by the action of dopamine or tetanic electrical stimulation of the corresponding afferent inputs in vitro are practically identical [5,7,8]. It was found that the level of activity of MNs (where dopamine induced LTP) observed in the behavior of the fishes increased nearly two times, as compared with that of MNs of intact and control (application of the same solution but with no dopamine) fishes.…”
Section: Introductionmentioning
confidence: 99%